Phase-change electromagnetic wave absorption film, preparation method and application thereof
By mixing electromagnetic wave absorbing powder with thermoplastic elastomer and adding sliced paraffin, the structural design problem of traditional wave absorbing materials on low thickness is solved, and efficient electromagnetic wave absorption performance and cost reduction is achieved, which is suitable for a variety of application needs.
Patent Information
- Application Number
- CN202411464447.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-10
AI Technical Summary
It is difficult for traditional absorbent materials to achieve effective structural design at low thickness, resulting in narrow absorption frequency bands, weak absorption performance, and complex process for flexible film preparation and lack of practicality.
The preparation method of phase-change electromagnetic wave absorption film is adopted. By mixing the electromagnetic wave absorption powder with the thermoplastic elastomer, dispersing it in an organic solvent, adding sliced paraffin, and heating and drying, a phase-change electromagnetic wave absorption film is formed to realize structural design and mechanics. Adjustable performance.
It has successfully achieved efficient electromagnetic wave absorption performance, reduced production costs, and has adjustability with mechanical properties and reversible conversion of films. It is suitable for different application needs and expanded the application range of films.
Smart Images

Figure CN119286014A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of microwave absorption, and in particular relates to a phase-change electromagnetic wave absorption film, a preparation method and application thereof. Background Art
[0002] Absorbing materials are a type of functional materials that can absorb incident electromagnetic waves and convert them into other forms of energy (such as heat). With the development of science and technology, such materials are increasingly used in military stealth, electromagnetic compatibility, electronic information and other fields. The classification of absorbing materials mainly includes magnetic loss type, resistance loss type and dielectric loss type, as well as coating type and structural type. Among them, thin film absorbing materials have significant advantages in stealth technology, electromagnetic compatibility of electronic equipment and other aspects due to their light weight, thinness and easy processing. Structural design has an important influence on the performance of electromagnetic wave absorbing materials, but it is difficult to achieve effective structural design of thin films at low thickness. In order to solve the shortcomings of traditional absorbing materials such as narrow absorption band and weak absorption performance, structural design is introduced. Through reasonable structural design and component regulation, the impedance matching of absorbing materials is optimized and efficient attenuation of electromagnetic waves is achieved. Nanocomposite technology, coating technology, laser induced processing, electrochemical deposition and other technologies are now widely used in the preparation of electromagnetic wave absorbing films, but these preparation methods are difficult to achieve structural design and are accompanied by problems such as difficulty in preparation and high cost. Therefore, developing a new method for preparing flexible thin film materials suitable for structural design will help further enhance the electromagnetic wave absorption performance of thin film absorbing materials. In current production, there are the following problems: 1. The preparation process of flexible films is relatively complicated. 2. It is difficult to achieve the structural construction of thin films prepared by traditional thin film preparation methods. 3. Traditional thin film structural design lacks practicality and process expansion. Therefore, designing a thin film preparation method that can realize the structural design of thin films is of great significance for achieving efficient electromagnetic wave absorption performance. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides a phase-change electromagnetic wave absorbing film, a preparation method and applications thereof.
[0004] A method for preparing a phase-change electromagnetic wave absorbing film comprises the following steps:
[0005] Mixing the electromagnetic wave absorbing powder with the thermoplastic elastomer and dispersing them in an organic solvent; stirring until the thermoplastic elastomer is dissolved in the organic solvent and the electromagnetic wave absorbing powder is dispersed in the thermoplastic elastomer solution;
[0006] Heat and continue stirring, then add sliced paraffin and dissolve to obtain a mixed solution;
[0007] The mixed liquid is transferred to a liquid tank, dried, and ventilated to obtain a phase-change electromagnetic wave absorbing film.
[0008] Preferably, the electromagnetic wave absorbing powder includes one or more of TPE, TPU, TPO and TPS.
[0009] Preferably, the mass ratio of the thermoplastic elastomer to the electromagnetic wave absorbing powder is 1:0.01-1:2.5.
[0010] Preferably, the drying temperature is 40-45°C.
[0011] Preferably, the drying air pressure is 0.1-0.5Mpa.
[0012] Preferably, the mass ratio of the sliced paraffin wax to the thermoplastic elastomer is 1:0.7-1:1.5.
[0013] Preferably, the drying time is 6-48 hours.
[0014] Preferably, the material of the liquid tank includes any one of glass or polytetrafluoroethylene.
[0015] The phase-change electromagnetic wave absorbing film is prepared by the above preparation method.
[0016] The above-mentioned phase-change electromagnetic wave absorbing film can be used in the production of electronic equipment.
[0017] The design scheme of the present invention successfully achieves adjustable mechanical properties and reversible conversion of film phase change, reducing production costs. On the basis of taking into account mechanical properties, it can be filled with other different types of powders according to film preparation requirements to ensure the scalability of application and be applicable to preparation requirements in different situations. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0019] Figure 1 For the selection of the ratio of paraffin wax and thermoplastic elastomer;
[0020] Figure 2 Schematic diagram of film drying: during transfer, oven drying, air drying, and finished product;
[0021] Figure 3 It is the physical picture of the film and the physical picture of the film with different structures;
[0022] Figure 4 is the optical cross-section image of the film;
[0023] Figure 5It is constructed for the corrugated membrane structure;
[0024] Figure 6 The structured film was measured by the arch method. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] The method for preparing a flexible phase-change electromagnetic wave absorbing film described in this patent includes the following steps:
[0028] Step 1: Mix 240 g of electromagnetic wave absorbing powder composed of carbonyl iron and 10 g of carbon fiber with 100 g of thermoplastic elastomer TPE, and disperse them in cyclohexane organic solvent.
[0029] Step 2: Stirring continuously at 80° C. for 2 hours until the thermoplastic elastomer is dissolved in the organic solvent and the absorber is fully dispersed in the thermoplastic elastomer solution.
[0030] Step 3, continue stirring at 80°C and add 100 g of slice paraffin wax to the mixture until the slice paraffin wax is completely dissolved.
[0031] Step 4, select 300x300 mm 2 Transfer the mixed solution in step 3 to the liquid tank.
[0032] Step 5, transfer the liquid tank with the liquid to a drying oven and dry it at 45° C. and 0.1 MPa for 6 h to remove most of the solvent.
[0033] Step 6, place the liquid tank in step 5 in a ventilated place and dry it for 144 hours to completely dry it, and take out the remaining film from the liquid tank.
[0034] Example 2
[0035] The method for preparing a flexible phase-change electromagnetic wave absorbing film described in this patent includes the following steps:
[0036] Step 1: Mix 120 g of ferric oxide, 3 g of carbon fiber and 1 g of silicon dioxide mixed powder with 70 g of thermoplastic elastomer TPU and disperse them in dimethyl sulfoxide.
[0037] Step 2: Stirring continuously at 100° C. for 3 hours until the thermoplastic elastomer is dissolved in the organic solvent and the absorber is fully dispersed in the thermoplastic elastomer solution.
[0038] Step 3, continue stirring at 80°C and add 30 g of slice paraffin wax to the mixture until the slice paraffin wax is completely dissolved.
[0039] Step 4, select 100x400 mm 2 Transfer the mixed solution in step 3 to the liquid tank.
[0040] Step 5, transfer the liquid tank with the liquid to a drying oven and dry it at 40° C. and 0.5 MPa for 48 hours to remove most of the solvent.
[0041] Step 6, place the liquid tank in step 5 in a ventilated place to dry for 72 hours to completely dry, and remove the remaining film from the liquid tank.
[0042] Example 3
[0043] The method for preparing a flexible phase-change electromagnetic wave absorbing film described in this patent includes the following steps:
[0044] Step 1: Mix electromagnetic wave absorbing powder consisting of 2 g of carbonyl iron and 0 g of carbon fiber with 200 g of thermoplastic elastomer TPE, and disperse them in cyclohexane organic solvent.
[0045] Step 2: Stirring continuously at 80° C. for 2 hours until the thermoplastic elastomer is dissolved in the organic solvent and the absorber is fully dispersed in the thermoplastic elastomer solution.
[0046] Step 3, continue stirring at 80°C and add 100 g of slice paraffin wax to the mixture until the slice paraffin wax is completely dissolved.
[0047] Step 4, select 300x300 mm 2 Transfer the mixed solution in step 3 to the liquid tank.
[0048] Step 5, transfer the liquid tank with the liquid to a drying oven and dry it at 45° C. and 0.1 MPa for 48 hours to remove most of the solvent.
[0049] Step 6, place the liquid tank in step 5 in a ventilated place and dry it for 144 hours to completely dry it, and take out the remaining film from the liquid tank.
[0050] Example 4
[0051] The method for preparing a flexible phase-change electromagnetic wave absorbing film described in this patent includes the following steps:
[0052] Step 1: Mix 240 g of electromagnetic wave absorbing powder composed of carbonyl iron and 10 g of carbon fiber with 150 g of thermoplastic elastomer TPE, and disperse them in cyclohexane organic solvent.
[0053] Step 2: Stirring continuously at 80° C. for 2 hours until the thermoplastic elastomer is dissolved in the organic solvent and the absorber is fully dispersed in the thermoplastic elastomer solution.
[0054] Step 3, continue stirring at 80°C and add 100 g of slice paraffin wax to the mixture until the slice paraffin wax is completely dissolved.
[0055] Step 4, select 300x300 mm 2 Transfer the mixed solution in step 3 to the liquid tank.
[0056] Step 5, transfer the liquid tank with the liquid to a drying oven and dry it at 45° C. and 0.1 MPa for 24 h to remove most of the solvent.
[0057] Step 6, place the liquid tank in step 5 in a ventilated place and dry it for 144 hours to completely dry it, and take out the remaining film from the liquid tank.
[0058] Example 5
[0059] The method for preparing a flexible phase-change electromagnetic wave absorbing film described in this patent includes the following steps:
[0060] Step 1: Mix 240 g of electromagnetic wave absorbing powder composed of carbonyl iron and 10 g of carbon fiber with 70 g of thermoplastic elastomer TPE, and disperse them in cyclohexane organic solvent.
[0061] Step 2: Stirring continuously at 80° C. for 2 hours until the thermoplastic elastomer is dissolved in the organic solvent and the absorber is fully dispersed in the thermoplastic elastomer solution.
[0062] Step 3, continue stirring at 80°C and add 100 g of slice paraffin wax to the mixture until the slice paraffin wax is completely dissolved.
[0063] Step 4, select 300x300 mm 2 Transfer the mixed solution in step 3 to the liquid tank.
[0064] Step 5, transfer the liquid tank with the liquid to a drying oven and dry it at 45° C. and 0.1 MPa for 24 h to remove most of the solvent.
[0065] Step 6, place the liquid tank in step 5 in a ventilated place and dry it for 144 hours to completely dry it, and take out the remaining film from the liquid tank.
[0066] Comparative Example 1
[0067] No paraffin was added, and the rest was the same as in Example 1.
[0068] In terms of electromagnetic wave absorption performance of Comparative Example 1, the film does not produce obvious differences in different polarization directions and the maximum absorption peak is near 17 GHz.
[0069] Taking carbonyl iron powder and carbon fiber as absorbers, TPE as thermoplastic elastomer, cyclohexane as organic solvent, and a circular groove with a diameter of 100 mm as an example, a method for preparing a flexible phase-change electromagnetic wave absorbing film is briefly described:
[0070] The electromagnetic wave absorbing powder composed of 36g of carbonyl iron and 1g of carbon fiber is mixed with 12g of thermoplastic elastomer TPE and dispersed in cyclohexane organic solvent. Stirring is continued at 80°C for 2.5h until the thermoplastic elastomer is dissolved in the organic solvent and the absorber is fully dispersed in the thermoplastic elastomer solution. Stirring is continued at 80°C, and 100g of sliced paraffin is added to the mixture until the sliced paraffin is completely dissolved. The mixture is then transferred to a liquid tank. The liquid tank with liquid is transferred to a drying oven and dried at 45°C and 0.1Mpa for 24h to remove most of the solvent. Then, the liquid tank is placed in a ventilated place and dried for 144h to completely dry, and the remaining film is taken out of the liquid tank. The ratio of paraffin wax to thermoplastic elastomer determines the mechanical properties of the final film, such as Figure 1 As shown in the figure, as the proportion of paraffin wax increases, its mechanical properties gradually tend to paraffin wax, and vice versa, its mechanical properties gradually tend to the flexibility of thermoplastic elastomer. In order to make the film achieve a balance between strength and flexibility, the mass ratio of paraffin wax to thermoplastic elastomer should be between 1:1.5 and 1:0.7.
[0071] In order to achieve a better final film-forming effect, the mass ratio of the absorber to the thermoplastic elastomer should be controlled between 0.1-2 to avoid the absorber being much larger than the thermoplastic elastomer, thereby causing damage to the film structure. Figure 2 As shown, from left to right are the liquid drying processes. As the drying proceeds, the liquid is gradually removed from the inside of the film.
[0072] The prepared flexible phase-change electromagnetic wave absorbing film is a flexible film in the heated state and gradually solidifies after cooling. Figure 2 As shown, a flat film sample is heated, bent or folded, and then cooled. Placing it on a plane can maintain its original shape without collapsing. After the bent or folded film is reheated, the original flat film can be restored, thereby achieving reversible conversion of the film structure. With the flat film as the node, any other shape can be converted by the route of "shape 1-flat film-shape 2", thereby achieving conversion of any two structures.
[0073] The film cross section was photographed with an optical microscope to determine its component distribution characteristics. It can be seen from the image that the components of the film are distributed relatively evenly, and there is no large amount of aggregation in local locations. Due to the uniform mixing of paraffin and TPE, the two components are intertwined, and the characteristics of paraffin and TPE can be achieved at the same time. That is, the phase change under the action of cold / hot fields and the elastic properties after softening.
[0074] On this basis, the film structure was simply designed. A wavy structure was adopted, with an amplitude of 2.75 mm and a period of 20 mm. Based on this, the film structure was constructed to achieve periodicity. The film was softened and shaped by heating the mold, and finally a film with periodic structure was prepared.
[0075] The film structure was tested by the arch method. Due to the construction of the film structure, the electromagnetic wave absorption performance of the film has significant differences under different polarization directions. Especially around 12.5GHz, due to the construction of the structure, the film has achieved additional enhancement in electromagnetic wave absorption performance. Finally, a total of 3.27GHz bandwidth (<-5dB) was achieved in the range of 11.85-13.75GHz and 15.11-16.48GHz.
[0076] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0077] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A method for preparing a phase-change electromagnetic wave absorbing film, characterized in that: The following steps are involved: Mixing the electromagnetic wave absorbing powder with the thermoplastic elastomer and dispersing them in an organic solvent; stirring until the thermoplastic elastomer is dissolved in the organic solvent and the electromagnetic wave absorbing powder is dispersed in the thermoplastic elastomer solution; Heat and continue stirring, then add sliced paraffin and dissolve to obtain a mixed solution; The mixed liquid is transferred to a liquid tank, dried, and ventilated to obtain a phase-change electromagnetic wave absorbing film.
2. The method for preparing a phase-change electromagnetic wave absorbing film according to claim 1, characterized in that: The electromagnetic wave absorbing powder includes one or more of TPE, TPU, TPO and TPS.
3. The method for preparing a phase-change electromagnetic wave absorbing film according to claim 1, characterized in that: The mass ratio of the thermoplastic elastomer to the electromagnetic wave absorbing powder is 1:0.01-1:2.
5.
4. The method for preparing a phase-change electromagnetic wave absorbing film according to claim 1, characterized in that: The drying temperature is 40-45°C.
5. The method for preparing a phase-change electromagnetic wave absorbing film according to claim 1, characterized in that: The air pressure of the drying is 0.1-0.5Mpa.
6. The method for preparing a phase-change electromagnetic wave absorbing film according to claim 1, characterized in that: The mass ratio of the sliced paraffin wax to the thermoplastic elastomer is 1:0.7-1:1.
5.
7. The method for preparing a phase-change electromagnetic wave absorbing film according to claim 1, characterized in that: The drying time is 6-48h.
8. The method for preparing a phase-change electromagnetic wave absorbing film according to claim 1, characterized in that: The material of the liquid tank includes any one of glass and polytetrafluoroethylene.
9. The phase-change electromagnetic wave absorbing film obtained by the preparation method according to any one of claims 1 to 8.
10. Application of the phase-change electromagnetic wave absorbing film according to claim 9 in the production of electronic equipment.